Does nuclear energy consumption contribute to human development? Modeling the effects of public debt and trade globalization in an OECD heterogeneous panel. (15th November 2022) - Sadiq, Muhammad; Wen, Fenghua; Bashir, Muhammad Farhan; Amin, Azka
Abstract: Global energy systems must be restructured to accommodate low-carbon energy sources and technologies to improve the socio-economic welfare of the state and reduce energy impacts on the environment. While nuclear energy has long been controversial, especially among environmentalists, numerous advocates now argue that it should be considered a clean energy source to boost human welfare, achieve energy security, and combat climate change. This research intends to study the properties of nuclear energy, public debt, trade globalization, and their impacts on human development in a heterogeneous panel of sixteen OECD nations for the dataset from 1990 to 2019 using the novel cross-sectional augmented autoregressive distributed lag model and Dumitrescu and Hurlin panel causality test. The empirical results suggest that nuclear energy and trade globalization boost human development, while higher public debt lowers human development in the long and short run. The findings recommend that the development and expansion of nuclear energy consumption and trade liberalization are crucial for enhancing the social welfare of OECD nations, which must also lower their public debt levels to achieve inclusive and sustainable growth. Graphical abstract: Image 1